PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP HASIL BELAJAR IPA SISWA PADA MATERI EKOSISTEM DI KELAS V MIS AL KHAIRAT DELI TUA TP 2023/2024 - Tarigan, Juniko Esra; Siregar, Hotma Tiolina; Zulianti, Sari Diella (JURNAL CURERE, 2024)
This research was conducted in class V of MIS AL-Khairat Deli Tua which consisted of 28 students in classes V-A and V-B. This type of research is quasi-experimental. This research aims to see the effect of using diorama media on students' science learning outcomes. The data obtained from this research is that there is a significant influence of the use of diorama media on students' science learning outcomes. This can be seen from the average score of class V-A students, namely 78, who are in the experimental class or who use diorama media, and the average score of class V-B students, namely 67.5, who are in the control class or who do not use diorama media. Thus, it can be concluded that the use of diorama media influences the science learning outcomes of class V students at MIS AL-Khairat Deli Tua.Keywords: Learning Media, Science Learning Outcomes